Pengaruh Intellectual Capital, Leverage, Kebijakan Dividen, dan Kualitas Audit Terhadap Earnings Management dengan Profitabilitas sebagai Variabel Moderasi - Hidayah, Firda Nur; Putra, Rosyid Nur Anggara (Journal of Islamic Economic Scholar, 2024)
Earnings management actions can occur in large and small companies, in financial and non-financial companies. Earnings management can occur when managers in reporting company finances use judgment for deviations in financial statement information on the basis of company performance. Factors that can motivate managers to practice earnings management are leverage, audit quality, and profitability. This study aims to determine how intellectual capital, leverage, dividend policy, and audit quality influence earnings management with profitability as a moderating variable. In this study, the population used was companies listed on the Jakarta Islamic Index 70 (JII70) for the 2015-2021 period. The sample selection was carried out using a purposive sampling technique so that as many as 20 companies were found that matched the research criteria, so that 140 research data were obtained. The data analysis technique used panel data regression with the help of the E-Views 12 statistical tool. The results showed that intellectual capital, leverage , dividend policy has no significant effect on earnings management, audit quality has a significant negative effect on earnings management, profitability is able to strengthen the effect of intellectual capital on earnings management, profitability cannot strengthen the effect of leverage and dividend policy on earnings management, profitability is able to strengthen the effect of audit quality on earnings management.